Biomasa y stock de carbono de una plantación con regeneración natural en zona inundable del distrito de Puinahua, Loreto. 2022 - Yumbato Hoyos, Danay Elena (2025)
The present research titled: “Biomass and carbon stock of a plantation with natural regeneration in a flood zone in the district of Puinahua, Loreto. 2022”, had the objective of estimating the biomass and carbon stock in a natural regeneration plantation in a flood zone. 17 forest and non-forest species from a 7.45 hectare plantation were evaluated. through an inventory. The results show a biomass of 322,625 kg in the entire plantation with naturally regenerative species, the capirona species concerns a high amount of biomass with 51,42466 kg. Furthermore, the height class from 50 cm to 69 cm indicates a biomass value (90,46017 kg), the height class from 30 cm 49 (78,32928 kg), the height class from 70 cm to 89 cm (63,25523 kg) and the height class of 90 to 109 cm (54,443 kg), respectively. The stored carbon of the entire plantation is 161,312 kgC, the capirona species contains the highest carbon captured with 25,71233 kgC. The height class from 50 cm to 69 cm indicates the highest stored carbon (45,23008 kgC), then the height class from 30 cm to 49 cm (39,16464 kgC), the height class from 70 to 89 cm (31,627 kgC) and the height class from 90 cm to 109 cm (27,22156 kgC). The height class of 110 a + cm definitely presents the lowest level of stored carbon with 18,06900 kgC.